Application of a New Approach Methodology (NAM)-based Strategy for Genotoxicity Assessment of Data-poor Compounds - Fortin, Anne-Marie (Université d'Ottawa / University of Ottawa, 2022)
The conventional battery for genotoxicity testing is not well-suited to assessing the large number of chemicals needing evaluation. Traditional in vitro tests lack throughput capacity, provide little mechanistic information, and have poor specificity in predicting in vivo genotoxicity. The Health Canada GeneTox21 research program is developing a multi-endpoint platform for modernized in vitro genotoxicity assessment. The GeneTox21 assays include the TGx-DDI transcriptomic biomarker (i.e., 64-gene expression signature to identify DNA damage-inducing (DDI) substances), the MicroFlow® assay (i.e., a flow cytometry-based micronucleus (MN) test), and the MultiFlow® assay (i.e., a multiplexed flow cytometry-based reporter assay that yields mechanism-of-action (MoA) information). As part of GeneTox21 development, the objective of this study was to investigate the utility of the TGx-DDI transcriptomic biomarker, multiplexed with the MicroFlow® and MultiFlow® assays, as an integrated testing strategy for screening data-poor substances prioritized by Health Canada’s New Substances Assessment and Control Bureau. Human lymphoblastoid TK6 cells were exposed to 3 control and 10 data-poor substances, using a 6-point concentration range. Cells were exposed for 4 hours with or without exogenous metabolic activation. Gene expression profiling was conducted using the targeted TempO-SeqTM assay, and the TGx-DDI classifier was applied to the dataset. Classifications were compared with those based on the MicroFlow® and MultiFlow® assays. Benchmark Concentration (BMC) modeling was used for potency ranking. The results of the integrated hazard calls indicate that five data-poor compounds are genotoxic in vitro, causing DNA damage via a clastogenic MoA, and one is positive via a pan-genotoxic MoA. Two compounds are likely irrelevant positives in the MN test; two are considered possibly genotoxic causing DNA damage via an ambiguous MoA. From quantitative analyses of concentration-response data, we observed nearly identical potency rankings for each assay with two main potency groups being observed. This ranking was maintained when all endpoint BMCs were converted into a single score using the Toxicological Prioritization (ToxPi) approach. Overall, this study contributes to the establishment of a modernized approach for effective genotoxicity assessment and chemical prioritization for further regulatory scrutiny. We conclude that integration of the TGx-DDI biomarker with other GeneTox21 assays is an effective NAM-based strategy for genotoxicity assessment of data-poor compounds.
Keywords: Genetic toxicology; TGx-DDI transcriptomic biomarker; New approach methodology; Data-poor compounds; Human health risk assessment; Toxicogenomics; MultiFlow®; MicroFlow®